OPM’s approach to assessing Value for Money - and King, Julian; OPM (Oxford Policy Management, 2018)
This document offers practical guidance for assessing value for money (VfM) in international development programmes. Since 2016, evaluation expert Julian King has been working with OPM to develop and deploy a robust approach to VfM assessment. The approach combines cutting-edge evaluation practice with concepts from economic evaluation to respond to donor requirements for accountability and good resource allocation, as well as to support reflection, learning, and adaptive management.